2010
DOI: 10.1186/1471-213x-10-39
|View full text |Cite
|
Sign up to set email alerts
|

Relative roles of the different Pax6 domains for pancreatic alpha cell development

Abstract: BackgroundThe transcription factor Pax6 functions in the specification and maintenance of the differentiated cell lineages in the endocrine pancreas. It has two DNA binding domains, the paired domain and the homeodomain, in addition to a C-terminal transactivation domain. The phenotype of Pax6-/- knockout mice suggests non-redundant functions of the transcription factor in the development of glucagon-expressing α-cells as this cell type is absent in the mutants. We ask the question of how the differentiation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…Although Pax6 positively regulates insulin and glucagon expression, it negatively regulates ghrelin expression and differentiation of -cells (Heller et al, 2005;Dames et al, 2010). Accordingly, miR-7 KD resulted in reduced numbers of ghrelinpositive cells (Fig.…”
Section: Mir-7 Controls Endocrine Differentiation In Cultured Explantsmentioning
confidence: 91%
See 1 more Smart Citation
“…Although Pax6 positively regulates insulin and glucagon expression, it negatively regulates ghrelin expression and differentiation of -cells (Heller et al, 2005;Dames et al, 2010). Accordingly, miR-7 KD resulted in reduced numbers of ghrelinpositive cells (Fig.…”
Section: Mir-7 Controls Endocrine Differentiation In Cultured Explantsmentioning
confidence: 91%
“…However, Pax6 negatively regulates the formation of ghrelin-expressing -cells (Sander et al, 1997;StOnge et al, 1997;Ashery-Padan et al, 2004;Heller et al, 2005;Dames et al, 2010). In both humans and mice, two Pax6 alleles are required in order to maintain proper glucose homeostasis, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It was further confirmed that the highly conserved Pax6 is a universal master control gene for eye development in the animal kingdom. Similar to the studied Pax6 genes in zebrafish 42 , Drosophila 36 , quail 43 , mouse [44][45][46] , and human 21,47,48 , the non-conserved C-terminus of the collembolan Pax6 is vital for protein transactivation ability. In our study, gradual deletions from the C-terminal end of collembolan Pax6 led to a gradual loss of activity in inducing ectopic eyes on Drosophila (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…However, more detailed investigation is required to determine whether these genes are targets or regulators of PAX6 expression or regulated by common upstream factors. If the PAX6 polymorphism changes the islet cell ratio, as is seen in mouse models with mutated Pax6 [34], this could also contribute to the many correlations. The most common cause for an increase in fasting insulin concentration is insulin resistance, also evidenced by an increase in the HOMA-IR.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies were performed in individuals with more severe mutations making generalisation of the findings to potential effects of common variants in the gene difficult. Further, there is evidence from mouse models that the effect of mutations and deletions in Pax6 on pancreatic development depends upon which functional domain of the protein is affected [34].…”
Section: Discussionmentioning
confidence: 99%